Comparison of Venom Extraction Methods of Bombus (Bombus) terrestris (Hymenoptera: Apidae: Bombus) by Using Bottom-up Proteomic Strategies - Pınar Barkan, Nezahat; Duygu Ozel Demiralp, Fatma; Murat Aytekin, Ahmet (Current Proteomics, 2015)
The aim of the study is to assess the influence of two different venom extraction methods, disruption of venom reservoir and manual milking, on the protein composition of Bombus (Bombus) terrestris venom. Through proteomic analyses, including determination of protein concentrations, two-dimensional gel electrophoresis, and peptide mass fingerprinting by matrix assisted laser desorption ionization/ time of flight mass spectrometry, we present that there is not a statistically significant discrepancy between protein profiles and expression levels of venoms obtained by the two methods. Disruption of the venom reservoir is more practical and venom shows no contamination when the method is performed carefully. Moreover, it is a more efficient alternative for bumble bees over milking which has time constraints.
Keywords: PMF